Create space for collaboration: can we help each other participate in participation? - Paul Sullivan (Scottish Journal of Residential Child Care, 2018)
This article is, in part, a celebration of Scotland's Year of Young People (YoYP) 2018. Year of Young People allows us a chance to promote and celebrate the fantastic talent of young people across Scotland. The 'Participation' theme of Year of Young People is a perfect example of this. As part of Year of Young People, CELCIS, alongside a wide range of partners, young people and communities involved in participation, are creating an exciting new space — the 'Participating in Participation Network' — where all of this great work can be amplified; and where people can be supported to learn from each other and share their own approach around participation. Recognising that currently in Scotland, there are thousands, probably millions, of young people and communities involved in participation work at any given time: People who are using their voice to change their world for the better; Who are contributing to their communities, or others, and using their passions, skills and experience to make a difference.This is an exciting time of change in Scotland, with a great deal of innovative practice, and we hope to share this excellent work via the participation network. This article offers an invite for interested parties to join the Participation Network and get involved in creating further change for children and young people